Fluorene‐Based Co‐polymer with High Hole Mobility and Device Performance in Bulk Heterojunction Organic Solar Cells. Issue 14 (5th June 2013) - Watters, Darren C.; Yi, Hunan; Pearson, Andrew J.; Kingsley, James; Iraqi, Ahmed; Lidzey, David
Abstract A new donor–acceptor polymer based on 9, 9‐dioctylfluorene is synthesized and tested in organic photovoltaic devices. Results show that the polymer exhibits good solubility in a range of organic solvents and has a high hole mobility. When blended with a PC70BM acceptor and fabricated into a bulk heterojunction, photovoltaic devices having a maximum power conversion efficiency (PCE) of 6.2% and a peak external quantum efficiency of 74% are created. Such efficiencies are realized without any necessity for solvent additives or thermal annealing protocols.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>